2018
DOI: 10.1080/14789949.2018.1477975
|View full text |Cite
|
Sign up to set email alerts
|

Do scores on the HCR-20 and FAM predict frequency of self-harm in females within a secure psychiatric hospital?

Abstract: Volume 1This volume consists of three chapters. The first chapter is a literature review examining whether there is a link between psychopathy and self-harm. The second chapter is a quantitative study investigating whether scores on the HCR-20 and FAM risk assessment tools predict frequency of self-harm in females within a secure psychiatric hospital. The third chapter comprises a public domain briefing document which provides a plain language summary of the literature review and empirical paper. Volume 2This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…The reconviction rate may be an underestimation of the actual recidivism because not all offenders are reported, apprehended, and arrested. Moreover, the outcome was only related to recidivism, while the FAM and START are also used to assess other types of risks, and both tools have previously been found to predict self-harm and inpatient violence (Campbell & Beech, 2018; O’Shea & Dickens, 2015). For future studies, it would be important to include other outcome measures, for instance, unofficial data on violence, data on victimization, and data on self-harm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reconviction rate may be an underestimation of the actual recidivism because not all offenders are reported, apprehended, and arrested. Moreover, the outcome was only related to recidivism, while the FAM and START are also used to assess other types of risks, and both tools have previously been found to predict self-harm and inpatient violence (Campbell & Beech, 2018; O’Shea & Dickens, 2015). For future studies, it would be important to include other outcome measures, for instance, unofficial data on violence, data on victimization, and data on self-harm.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the psychometric properties of the FAM, only preliminary results from small samples are available. They show good interrater reliability and moderate to good predictive validity for inpatient violence, threatening behavior, and self-harm during treatment (Campbell & Beech, 2018; de Vogel et al, 2014; Greig, 2014; Griswold et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Borderline personality disorder was also associated with an increased risk of suicide attempts (Stinson and Gonsalves, 2013). Further, receiving a diagnosis of a personality disorder in general was associated with an increased risk of self-harm (Beasley, 1999;Campbell and Beech, 2018;Girardi et al, 2021;O'Shea et al, 2014;Selenius et al, 2016), as well as being involved in more incidents of self-harm compared to those without a diagnosis of personality disorder (Girardi et al, 2021). Psychopathy was also associated with self-harm (Swinton et al, 1998), as well as traits of psychopathy, such as grandiose and manipulative/coercive interpersonal style and glib presentation (Daffern et al, 2010;Das et al, 2007;Vernham et al, 2015).…”
Section: Analysis Of Themesmentioning
confidence: 99%
“…The Historical, Clinical and Risk (HCR-20) Management scale was evaluated in two studies (Campbell & Beech, 2018;O'Shea, Picchioni, Mason, Sugarman, & Dickens, 2014). It was found that higher mean total scores on HCR-20 were associated with more frequent self-harm (p < 0.001) (Campbell & Beech, 2018); however, effect sizes were not large enough (0.345-0.749) to support the use of HCR-20 in practice . Madan et al (2016) reported findings that provide some support for the reliability and validity of the C-SSRS related to its potential to correctly predict suicide-related behavior (p < 0.01).…”
Section: Suicide and Self-harm Related Outcomesmentioning
confidence: 99%